PET-guided eBEACOPP treatment of advanced-stage Hodgkin lymphoma (HD18): follow-up analysis of an international, open-label, randomised, phase 3 trial. Issue 6 (June 2021) - Kreissl, Stefanie; Goergen, Helen; Buehnen, Ina; Kobe, Carsten; Moccia, Alden; Greil, Richard; Eichenauer, Dennis A; Zijlstra, Josée M; Markova, Jana; Meissner, Julia; Feuring-Buske, Michaela; Soekler, Martin; et al.
Summary: Background: The German Hodgkin Study Group's HD18 trial established the safety and efficacy of PET-guided eBEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone in escalated doses) for the treatment of advanced-stage Hodgkin lymphoma. However, because of a protocol amendment during the enrolment period (June 1, 2011) that changed standard treatment from eight to six cycles, the results of the HD18 trial have been partially immature. We report a prespecified 5-year follow-up analysis of the completed HD18 trial. Methods: HD18 was an international, open-label, randomised, phase 3 trial done in 301 hospitals and private practices in five European countries. Patients aged 18–60 years with newly diagnosed, advanced-stage Hodgkin lymphoma and an Eastern Cooperative Oncology Group performance status of 0–2 were recruited. After receiving an initial two cycles of eBEACOPP (1250 mg/m 2 intravenous cyclophosphamide [day 1], 35 mg/m 2 intravenous doxorubicin [day 1], 200 mg/m 2 intravenous etoposide [day 1–3], 100 mg/m 2 oral procarbazine [day 1–7], 40 mg/m 2 oral prednisone [day 1–14], 1·4 mg/m 2 intravenous vincristine [day 8], and 10 mg/m 2 intravenous bleomycin [day 8]), patients underwent a contrast-enhanced CT and PET scan (PET-2). Patients with positive PET-2 were randomly assigned to receive standard therapy (an additional six cycles of eBEACOPP; ie, eight cycles in total) or experimental therapy (an additional six cycles of eBEACOPP plus 375 mg/m 2 intravenous rituximab; ie, eight cycles in total) until June 1, 2011. After June 1, 2011, all patients with positive PET-2 were assigned to the updated standard therapy with an additional four cycles of eBEACOPP (ie, six cycles in total). Patients with negative PET-2 were randomly assigned (1:1) to receive standard therapy (an additional six cycles of eBEACOPP [ie, eight cycles in total] until June 1, 2011; an additional four cycles of eBEACOPP [ie, six cycles in total] after June 1, 2011) or experimental therapy (an additional two cycles of eBEACOPP; ie, four cycles in total). Randomisation was done centrally with the minimisation method, including a random component, stratified by centre, age, stage, international prognostic score, and sex. The primary endpoint was progression-free survival. HD18 aimed to improve 5-year progression-free survival by 15% in the PET-2-positive intention-to-treat cohort and to exclude inferiority of 6% or more in 5-year progression-free survival in the PET-2-negative per-protocol population. This study is registered with ClinicalTrials.gov, NCT00515554, and is completed. Findings: Between May 14, 2008, and July 18, 2014, 2101 patients were enrolled and 1945 were assigned to a treatment group according to their PET-2 result. In the PET-2-positive cohort, with a median follow-up of 73 months (IQR 59 to 94), 5-year progression-free survival was 89·9% (95% CI 85·7 to 94·1) in 217 patients assigned to eight cycles of eBEACOPP before the protocol amendment and 87·7% (83·1 to 92·4) in 217 patients assigned to eight cycles of rituximab plus eBEACOPP (p=0·40). Among 506 patients who received six cycles of eBEACOPP after the protocol amendment, 5-year progression-free survival was 90·1% (95% CI 87·2 to 92·9), with a median follow-up of 58 months (IQR 39 to 66). In the PET-2-negative cohort, with a median follow-up of 66 months (IQR 54 to 85) in the combined pre-amendment and post-amendment groups, 5-year progression-free survival was 91·2% (95% CI 88·4 to 93·9) in 446 patients who received eight or six cycles of eBEACOPP and 93·0% (90·6 to 95·4) in 474 patients who received four cycles of eBEACOPP (difference 1·9% [95% CI −1·8 to 5·5]). In the subgroup of PET-2-negative patients randomly assigned after protocol amendment, 5-year progression-free survival was 90·9% (95% CI 86·8 to 95·1) in 202 patients assigned to receive six cycles of eBEACOPP and 91·0% (86·6 to 95·5) in 200 patients assigned to receive four cycles of eBEACOPP (difference 0·1% [–5·9 to 6·2]). Interpretation: Long-term follow-up confirms the efficacy and safety of PET-2-guided eBEACOPP in patients with advanced-stage Hodgkin lymphoma. The reduction from eight to four cycles of eBEACOPP represents a benchmark in the treatment of early-responding patients, who can now be potentially cured with a short and safe treatment approach. Funding: Deutsche Krebshilfe, Swiss State Secretariat for Education, Research and Innovation SERI (Switzerland), and Roche Pharma. Translation: For the German translation of the abstract see Supplementary Materials section.